TRADISI LOKAL SEBAGAI PENANDA IDENTITAS: RESPON KEAGAMAAN TERHADAP TANTANGAN GLOBALISASI - Opi Irawansah; Melyana R Pugu (CV. Adiba Aisha Amira, 2025)
Local traditions play an important role as markers of community identity amid the increasingly complex challenges of globalisation. This study aims to analyse how local religious traditions respond to global changes, emphasising the processes of adaptation and resistance that occur at the community level. Through a literature review method, this study found that the adaptation of local religious traditions occurs not only in ritual aspects but also in the underlying values, influenced by the role of religious elites, the younger generation, government policies, and digital technology. On the other hand, resistance emerges as an effort to preserve spiritual meaning and cultural identity amid the tide of global homogenisation. The findings indicate that the success of preserving traditions as markers of identity depends heavily on the community's ability to balance the preservation of noble values with creative innovation, ensuring that local traditions remain relevant and serve as a source of inspiration in the era of globalisation.